The Annona montana genome reveals the development and flavor formation in mountain soursop fruit - Guangda Tang; Guizhen Chen; Jianhao Ke; Jieyu Wang; Diyang Zhang; Dingkun Liu; Jie Huang; Sijin Zeng; Miao Liao; Xuefen Wei; Zihao Huang; Minghui Ou; et al. (Ornamental Plant Research, 2023)
Annona is a genus of family Annonaceae within the magnoliids and plays a crucial role in revealing the evolution of magnolias. Annona species provide important fruit resources. Here, we report a chromosome-level genome assembly of A. montana, an edible and ornamental fruit species. Integration with other genomes provides clear evidence that the magnoliids were sisters to eudicots, and the ASTRAL trees showed discordance in the phylogenetic position of magnoliids, which might be caused by incomplete lineage sorting (ILS). Whole genome duplication (WGD) analysis showed that the common ancestor of A. montana and Liriodendron chinense experienced a WGD event, and this WGD event occurred after the splitting of Magnoliales and Laurales. We identified the gene family expansions and contractions in Annonaceae. Based on the identification of MADS-box gene families, we inferred the pathway integrators of morphological regulation, the occurrence of florescence and the development of fruit in A. montana. In addition, we identified key sugar transporter genes and the key enzyme genes related to sugar accumulation in A. montana fruit. The gene function analysis indicated that starch and cell wall degradation might be the main reasons for the softening of A. montana fruit. Furthermore, aromatic alcohols were suggested be the main volatile aromatic compounds in A. montana fruit. Our results provide the genetic basis of fruit development, softening, aroma, and sugar accumulation in A. montana and the evolution and diversification of Annonaceae.